High-Molecular-Weight FK506-Binding Proteins Are Components of Heat-Shock Protein 90 Heterocomplexes in Wheat Germ Lysate - Reddy, Ramachandra K. (American Society of Plant Physiologists, 1998)
In animal cell lysates the multiprotein heat-shock protein 90 (hsp90)-based chaperone complexes consist of hsp70, hsp40, and p60. These complexes act to convert steroid hormone receptors to their steroid-binding state by assembling them into heterocomplexes with hsp90, p23, and one of several immunophilins. Wheat germ lysate also contains a hsp90-based chaperone system that can assemble the glucocorticoid receptor into a functional heterocomplex with hsp90. However, only two components of the heterocomplex-assembly system, hsp90 and hsp70, have thus far been identified. Recently, purified mammalian p23 preadsorbed with JJ3 antibody-protein A-Sepharose pellets was used to isolate a mammalian p23-wheat hsp90 heterocomplex from wheat germ lysate (J.K. Owens-Grillo, L.F. Stancato, K. Hoffmann, W.B. Pratt, and P. Krishna [1996] Biochemistry 35: 15249–15255). This heterocomplex was found to contain an immunophilin(s) of the FK506-binding class, as judged by binding of the radiolabeled immunosuppressant drug [(3)H]FK506 to the immune pellets in a specific manner. In the present study we identified the immunophilin components of this heterocomplex as FKBP73 and FKBP77, the two recently described high-molecular-weight FKBPs of wheat. In addition, we present evidence that the two FKBPs bind hsp90 via tetratricopeptide repeat domains. Our results demonstrate that binding of immunophilins to hsp90 via tetratricopeptide repeat domains is a conserved protein interaction in plants. Conservation of this protein-to-protein interaction in both plant and animal cells suggests that it is important for the biological action of the high-molecular-weight immunophilins.